Timor Leste Community Perceptions About the Use of Portugal Language in Telejornal News on Television Radio E Televisaun de Timor Leste Empreza Publica (RTTL, EP) - Patricia Baliana Da Costa; Reza Safitri; Bambang Dwi Prasetyo (International Journal of Science and Society, 2022)
This research is motivated by the different perceptions among the people of Lautem district, Tutuala sub-district, Timor Leste about the use of Portuguese in the Telejornal RTTL'EP news. In its reporting, Telejornal uses two language versions, namely Tetum and Portuguese. However, in the Tetum version of the news, it is more dominated by Portuguese which is generally not understood by the public. PThis study aims to determine the perception and understanding of the people of Timor Leste about the use of Portuguese in the news of Telejornal Rádio e Televisão de Timor Leste Empresa Publica (RTTL, EP) and how the people of Timor Leste interpret Portuguese itself. The approach of this research is descriptive qualitative research with the number of informants as many as 25 people, with data collection techniques through in-depth interviews and documentation.The results showed that only 13% of the people understood Portuguese and the remaining 87% of the people did not understand Portuguese through the newsTelejornal.This is due to the different understandings of the people of the Tutuala sub-district according to generations from three different eras, namely the Portuguese era generation, the Indonesian era generation and the generation after independence. In addition, Portuguese for the people of the Tutuala sub-district is interpreted as a foreign language/language of another nation/Bulenese language which is unable to unite the people of Timor Leste with different cultural backgrounds. In the end, this phenomenon created discomfort for the people of Timor Leste so that people preferred foreign television channels, namely Indonesian television broadcasts, rather than Telejornal RTTL, EP broadcasts.